Elemental Distributions and Mineral Parageneses of the Skaergaard PGE–Au Mineralization: Consequences of Accumulation, Redistribution, and Equilibration in an Upward-Migrating Mush Zone. (5th December 2019) - Nielsen, T F D; Rudashevsky, N S; Rudashevsky, V N; Weatherley, S M; Andersen, J C Ø
Abstract: The Skaergaard PGE–Au mineralization, aka the Platinova Reef, is a syn-magmatic Platinum Group Element (PGE) and gold (Au) mineralization that formed after crystallization of ∼74% of the bulk melt of the intrusion. It is hosted in a more than 600 m deep and bowl-shaped succession of gabbroic macro-rhythmic layers in the upper 100 m of the Middle Zone. The precious metal mineralization comprises a series of concordant, but compositionally zoned, mineralization levels identified by distinct PGE, Au and Cu peaks. They formed due to local sulphide saturation in stratiform concentrations of interstitial and evolved mush melts in six MLs over > 2000 years. The PGE–Au mineralization is compared to a stack of gold-rimmed saucers of PGE-rich gabbro of upward decreasing size. Fundamentally different crystallization and mineralization scenarios have been proposed for the mineralization, including offset reef type models based on sulphide saturation in the melt from which the silicate host crystallized, and the here argued model which restricts the same processes to the melt of the inward migrating mush zone of the magma chamber. The latter is supported by: i) a 3 D summary of the parageneses of precious metal minerals and phases (> 4000 grains) from 32 samples across the mineralization; ii) a 3 D compilation of all bulk rock assay data; and iii) a principal component analysis (PCA) of PGE, Au, Cu, and selected major and trace elements. In the main PGE-mineralization level (Pd5 alias Pd-Zone) the precious metal mineral paragenesis varies across the intrusion with precious metal sulphides and Au-alloys at the W-margin to Precambrian basement, precious metal plumbide and Au- and Ag-alloys at the E-margin to flood basalts, and skaergaardite (PdCu) and intermetallic compounds and alloys of PGE–Au and Cu in the central parts of the mineralization. Precious metal parageneses are distinct for a given sector of the intrusion, i.e. drill core (local control), rather than for a given stratigraphic or temporal interval in the accumulated gabbros. The precious metal 'grade times width' number (average g/t x metres) for the mineralization at an upper and a lower cut off of 100 ppb PGE or Au increases from ∼20 to ∼45 g toward the centre of the mineralization due to ponding of precious metal bearing melt. A strong increase in (Pd+Pt+Au)/Cu and dominance of (PdCu) alloys in the lower and central parts of the mineralization demonstrate the partial dissolution of droplets of Cu-rich sulphide melt and fractionation of precious metal ratios. The precious metal parageneses, the distribution of precious metals in the mineralization, and the PCA support initial accumulation of precious metals in the melt of the mush in the floor, followed by equilibration, sulphide saturation, and reactions with residual and immiscible Fe-rich silicate melt in a series of macro-rhythmic layers in the stratified and upward migrating mush zone in the floor of the magma chamber. Syn-magmatic and upward redistribution of precious metals sets the Skaergaard PGE–Au Mineralization apart from conventional reef type and offset-reef type precious metal mineralizations, and characterize 'Skaergaard type' precious metal deposits.